BBK07 Immunodominant Peptides as Serodiagnostic Markers of Lyme Disease - Coleman, Adam S. (American Society for Microbiology (ASM), 2011)
Lyme disease (LD) is a tick-borne infection caused by the bacterial pathogen Borrelia burgdorferi. Current diagnostic tests mostly use borrelial lysates or select antigens to detect serum antibodies against B. burgdorferi. These immunoassays are not entirely effective, especially for detection of early infection. We have recently characterized an in vivo-induced antigen, BBK07, as a serodiagnostic marker for LD. We now report that in a line blot assay, recombinant BBK07 protein-based detection is 90% sensitive and nearly 100% specific against B. burgdorferi infection in humans. Using an overlapping peptide library of 23 peptides encompassing full-length BBK07, we identified the immunodominant epitopes of BBK07 during human infection. We show that a select combination of amino-terminal peptides significantly enhanced BBK07-based diagnostic accuracy compared to that with the full-length protein. Although in enzyme-linked immunosorbent assay (ELISA) studies BBK07 peptides had overall lower sensitivity than established serodiagnostic peptides, such as the VlsE peptide C6 and OspC peptide pepC10, for the detection of early human LD, a subset of serum samples that failed to recognize either VlsE or OspC peptides were preferentially reactive to BBK07 peptides. These results highlight the fact that BBK07 peptides could be useful to complement the efficacy of VlsE and OspC peptide-based serodiagnostic assays. Finally, using a panel of canine sera, we show that BBK07 peptide is also effective for LD diagnosis in infected dogs. Together, our data show that peptides from the B. burgdorferi surface protein BBK07 are highly specific and sensitive serodiagnostic markers, and we suggest their future use in LD diagnostic assays.